SISTEM INFORMASI HUKUM PERLINDUNGAN ANAK - Hariani, Sutik (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2007)
System is any identifiable assemble of element (object person aktivities information records etc) which are interrelated by process or structure and which are presumed to function as on organizational entity generating on observable (or sometimes merely inferable) product (ryans 1968).